POLITENESS STRATEGY PERFORMED IN SATU JAM LEBIH DEKAT TALK SHOW ON TV ONE: A PRAGMATIC APPROACH - Syah, Nur Aini (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2021)
Talk show program on TV One is a program that uses language as a means of communication. To create the success of cummunication, it needs a strategy. This study aims to find out the politeness srategies used in Satu Jam Lebih Dekat talk show on TV One. The method used in this article is descriptive qualitative method. The data source of this research is oral data source, which is focused on the speeches between the presenter, interviewees, and mystery guest with the sources from a number of ministers in our country by downloading on the site www.youtube.com. For data analysis technique, the researcher used the contextual method with the pragmatic competence-in-dividing. And for the theory, the researcher focuses on politeness strategies by Brown Levinson's theory (1987: 94).The results indicate that there are 16 types of politeness strategies of Satu Jam Lebih Dekat program namely Bald on record, Positive Politeness-attend to hearer, Positive Politeness-intensify interest, Positive Politeness-use group identify marker, Positive Politeness-seek agreement, Positive Politeness-avoid disagreement, Positive Politeness-assert speaker’s knowledge, Positive Politeness-include both speaker and hearer in activity, Positive Politeness-give or ask reasons, Positive Politeness-give gifts, Negative Politeness-be conventionally indirect, Negative Politeness-question, hedge, Negative Politeness-give deference, Negative Politeness-impersonalize speaker and hearer, Off record-give hints, and Off record-give association clues. The most dominant use of politeness strategy is positive politeness-asking an agreement with the 42 percentage. The politeness strategies of this speech acts support the effectiveness of talk show and will minimize threats, protect, and extract information from interviewees without any compulsion due to the use of this politeness strategy.